Understanding the background and clinical significance of the WHO, WOAH, and EMA classifications of antimicrobials to mitigate antimicrobial resistance - Gehring, Ronette; Mochel, Jonathan P.; Schmerold, Ivo (Frontiers in Veterinary Science, 2023)
In Europe, the classification systems of the WHO, WOAH (founded as OIE), and EMA are the prevailing standard documents guiding the prudent use of antibiotic substances. While the WHO document “Critically important antimicrobials for human medicine” eponymously focusses on the use in humans, the other two documents, “OIE List of Antimicrobial Agents of Veterinary Importance” and “EMA Categorization of antibiotics for use in animals,” concentrate exclusively on the prudent use of antibiotics in animals. One common purpose of these classification systems is to provide guidance in making sound decisions on the choice of antibiotics for treating humans as well as animals. Although the latest editions of these compendia refer to one another and bear a clear resemblance at the category levels, some of the substances are grouped into unequal classes. This review illustrates the specific perspectives of the three categorization systems under consideration. The arguments raised for different classifications between the WHO and the EMA are exemplified for amoxicillins without beta-lactamase inhibitors, macrolides, sulfonamides, and colistin. For the daily clinical use of antibiotics, veterinarians should consider the EMA document, and, under tentative circumstances, consult the OIE list.